"For their own good" : civilian evacuations in Germany and France, 1939 - 1945 - Torrie, Julia S. 1973- (Berghahn Books, 2010)
Preparing for air war -- Order or chaos? -- Organizing evacuations -- Our stay gives us no pleasure -- If only family unity can be maintained -- On the basis of selection -- Responding to chaos -- Evacuation's aftermath